Tomato-oleoresin supplement prevents doxorubicin-induced cardiac myocyte oxidative DNA damage in rats - Ferreira, Ana Lúcia dos Anjos [UNESP]; Salvadori, Daisy Maria Favero [UNESP]; Munhoz Oliveira Nascimento, Maria Carolina; Rocha, Noeme Sousa [UNESP]; Corrêa, Camila Renata [UNESP]; Pereira, Elenize Jamas; Matsubara, Luiz Shiguero [UNESP]; Matsubara, Beatriz Bojikian [UNESP]; Placido Ladeira, Marcelo Sady (Elsevier B.V., 2007)
Doxorubicin (DOX) is an efficient chemotherapeutic agent used against several types of tumors; however, its use is limited due to severe cardiotoxicity. Since it is accepted that reactive oxygen species are involved in DOX-induced cardiotoxicity, antioxidant agents have been used to attenuate its side effects. To determine tomato-oleoresin protection against cardiac oxidative DNA damage induced by DOX, we distributed Wistar male rats in control (C), lycopene (L), DOX (D) and DOX+lycopene (DL) groups. They received corn oil (C, D) or tomato-oleoresin (5 mg/kg body wt. day) (L, DL) by gavage for a 7-week period. They also received saline (C, L) or DOX (4 ma/kg body wt.) (D, DL) intraperitoneally at the 3rd, 4th, 5th, and at 6th week. Lycopene absorption was checked by HPLC. Cardiac oxidative DNA damage was evaluated by the alkaline Comet assay using formamidopyrimidine-DNA glycosylase (FPG) and endonuclease III (endo 111). Cardiomyocyte levels of SBs, SBs FPG and SBs Endo III were higher in rats from D when compared to other groups. DNA damage levels in cardiomyocytes from DL were not different when compared to C and L groups. The viability of cardiomyocytes from D or DL was lower than C or L groups (p < 0.01). Lycopene levels (mean +/- S.D. nmol/kg) in saponified hearts were similar between L (47.43 +/- 11.78) and DL (49.85 +/- 16.24) groups. Our results showed: (1) lycopene absorption was confirmed by its cardiac levels; (2) DOX-induced oxidative DNA damage in cardiomyocyte; (3) tomato-oleoresin supplementation protected against cardiomyocyte oxidative DNA damage. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: cardiotoxicity; DNA damage; doxorubicin; HPLC; lycopene; rat